Improving Students' Speaking Skill of the 11th Grade through TikTok Application in Narrative Text at SMKN 2 Magelang - Harahap , Amin Said; Priyana, Joko; Faizal, Abdul Azis (EDUPEDIA Publisher, 2023)
Using the correct resources helps enhance EFL and Indonesian speaking abilities. TikTok is a social media platform that may be used as a teaching tool to amuse students, enhance their knowledge, and disseminate educational content. TikTok is popular among EFL students. Many people assume English is difficult and compulsory. English is commonly cited as a workplace ability. Many organizations desire English-speaking personnel. Communication is key. This research examines the usefulness of TikTok as a medium for teaching English to 11th-grade management business students at SMK N 2 Magelang. The population was 11th grade business and management students at SMKN 2 Magelang in 2022-2023, comprising 36 students chosen by purposive sampling. This study used a teacher's interview guideline, student's interview guideline, students' observation checklist, pre test and post test to collect data, which aimed to explain the situation in class activities, individual involvement in some activities, and the relationship between situation, activity, and individual. Open-ended questions were utilized to obtain data. After collecting data, it was evaluated qualitatively and quantitatively to explain observations and tests. The result showed that pupils' speaking abilities increased from the first to second cycle. Second cycle mean: 69.11 Scores and mean were improved in the second cycle. The percentage of pupils scoring >56 rose. Four students (16.0%) scored >56 on the pre-test. 8 (32.0%) cycle I post-test students scored >64. 10 students (40.0%) scored >76 on cycle II's post-test.